Forests, Trees, and Micronutrient-Rich Food Consumption in Indonesia - Ickowitz, A.; Rowland, D.; Powell, B.; Salim, M.A.; Sunderland, Terry C.H. (Public Library of Science, 2016)
Micronutrient deficiency remains a serious problem in Indonesia with approximately 100 million people, or 40% of the population, suffering from one or more micronutrient deficiencies. In rural areas with poor market access, forests and trees may provide an essential source of nutritious food. This is especially important to understand at a time when forests and other tree-based systems in Indonesia are being lost at unprecedented rates. We use food consumption data from the 2003 Indonesia Demographic Health Survey for children between the ages of one and five years and data on vegetation cover from the Indonesian Ministry of Forestry to examine whether there is a relationship between different tree-dominated land classes and consumption of micronutrient-rich foods across the archipelago. We run our models on the aggregate sample which includes over 3000 observations from 25 provinces across Indonesia as well as on sub-samples from different provinces chosen to represent the different land classes. The results show that different tree-dominated land classes were associated with the dietary quality of people living within them in the provinces where they were dominant. Areas of swidden/agroforestry, natural forest, timber and agricultural tree crop plantations were all associated with more frequent consumption of food groups rich in micronutrients in the areas where these were important land classes. The swidden/agroforestry land class was the landscape associated with more frequent consumption of the largest number of micronutrient rich food groups. Further research needs to be done to establish what the mechanisms are that underlie these associations. Swidden cultivation in is often viewed as a backward practice that is an impediment to food security in Indonesia and destructive of the environment. If further research corroborates that swidden farming actually results in better nutrition than the practices that replace it, Indonesian policy makers may need to reconsider their views on this land use.